Trees as Protein Sources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Trees with high-protein Ieaves are proving to be a valuable and practical feed resource for cattle, sheep, goats, and pigs in several Caribbean countries. In many instances one or more of a range of nitrogen-fixing species are grown to complement...